Experimental Infection of Mexican Free-Tailed Bats (Tadarida brasiliensis) with SARS-CoV-2 - J. S. Hall; E. Hofmeister; H. S. Ip; S. W. Nashold; A. E. Leon; C. M. Malavé; E. A. Falendysz; T. E. Rocke; M. Carossino; U. Balasuriya; S. Knowles (mSphere, 2023)
ABSTRACT The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus is thought to have originated in wild bats from Asia, and as the resulting pandemic continues into its third year, concerns have been raised that the virus will expand its host range and infect North American wildlife species, including bats. Mexican free-tailed bats (Tadarida brasiliensis) live in large colonies in the southern United States, often in urban areas and, as such, could be exposed to the virus from infected humans. We experimentally challenged wild T. brasiliensis with SARS-CoV-2 to determine the susceptibility, reservoir potential, and population impacts of infection in this species. Of 10 bats oronasally inoculated with SARS-CoV-2, 5 became infected and orally excreted moderate amounts of virus for up to 18 days postinoculation. These five subjects all seroconverted and cleared the virus before the end of the study with no obvious clinical signs of disease. We additionally found no evidence of viral transmission to uninoculated subjects. These results indicate that while T. brasiliensis are susceptible to SARS-CoV-2 infection, infection of wild populations of T. brasiliensis would not likely cause mortality. However, the transmission of SARS-CoV-2 from T. brasiliensis to or from humans, or to other animal species, is a possibility requiring further investigation to better define. IMPORTANCE As the COVID-19 pandemic has continued for 3+ years, there has been increasing concern that the SARS-CoV-2 virus will enter wildlife populations and potentially create new reservoirs where the virus could adapt to a new host and create variants. This is particularly possible with species that reside in man-made structures, in proximity to infected human populations. Mexican free-tailed bats (Tadarida brasiliensis) live in large colonies, often in urban settings and, thus, can be exposed by infected humans and potentially transmit the virus to new hosts. We experimentally challenged T. brasiliensis with SARS-CoV-2 and revealed that they are susceptible to the virus and excrete moderate amounts for up to 18 days postinoculation. This is important information for wildlife biologists, wildlife rehabilitation workers, and the general public that may contact these animals.